Role Conflict, Role Overload, and Work and Family Conflict: The Moderating Marital Status - Azis Rahman Sulfan; Syahrizal Syahrizal (Human Resource Management Studies, 2022)
This study aims to determine the effect of role conflict and role overload on work family conflicts with marital status as a moderating variable. This study uses five high schools in the city of Bukittinggi. The population in this study were high school teachers in the city of Bukittinggi. While the sample used amounted to 82 teachers. Data collection is done through distributing questionnaires and data processing is done through smart PLS3. The results of this study indicate that role conflict has a positive and significant effect on work and family conflict, role overload does not significantly affect work family conflict, marital status significantly moderates the relationship between role conflict and work and family conflict, marital status does not significantly moderate the relationship between role overload to work and family conflicts.